2019
DOI: 10.1038/s41467-019-13326-8
|View full text |Cite
|
Sign up to set email alerts
|

Chiral donor–acceptor azetines as powerful reactants for synthesis of amino acid derivatives

Abstract: Coupling reactions of amines and alcohols are of central importance for applications in chemistry and biology. These transformations typically involve the use of a reagent, activated as an electrophile, onto which nucleophile coupling results in the formation of a carbon-nitrogen or a carbon–oxygen bond. Several promising reagents and procedures have been developed to achieve these bond forming processes in high yields with excellent stereocontrol, but few offer direct coupling without the intervention of a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Consistent with our previous report, [13] DACPs that contain an ester group undergo ring openingw ith aqueous solutions of strong nucleophilest or esulti np roducts of nucleophilic substitution at an ester group, and at least two equivalents of as trongn ucleophile is required to complete the reaction. [24] DACP 2a upon treatment with excess (2.5 equiv) hydrazine hydrate, a5 0% aqueouss olution of hydroxylamine, and a3 4% aqueous solution of ammonia formed the corresponding dihydrazide 9 (88 %y ield), dihydroxamic acid 10 (82 %y ield), and diamide 11 (92 %y ield) that are highlys oluble in water but not in organics olvents (Scheme 3).…”
Section: Reactions Copesupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with our previous report, [13] DACPs that contain an ester group undergo ring openingw ith aqueous solutions of strong nucleophilest or esulti np roducts of nucleophilic substitution at an ester group, and at least two equivalents of as trongn ucleophile is required to complete the reaction. [24] DACP 2a upon treatment with excess (2.5 equiv) hydrazine hydrate, a5 0% aqueouss olution of hydroxylamine, and a3 4% aqueous solution of ammonia formed the corresponding dihydrazide 9 (88 %y ield), dihydroxamic acid 10 (82 %y ield), and diamide 11 (92 %y ield) that are highlys oluble in water but not in organics olvents (Scheme 3).…”
Section: Reactions Copesupporting
confidence: 90%
“…To obtain access to monosubstituted succinic mixed diesters and amidoesters we optimized DACP formation—ring opening of 4‐substituted enoldiazo‐acetates 1 a and 1 b and ‐acetamide 4 b with primary and secondary alcohols (Table 5). Our previous studies on ring opening of donor–acceptor azetines [13] indicated that the reaction was sluggish with methanol and primary alcohols, occurred only at elevated temperatures, and did not occur with secondary or tertiary alcohols. The ring opening of silyl‐protected donor–acceptor cyclobutenes with methanol (but not with primary, secondary or tertiary alcohols) occurred at room temperature in the presence of DMAP (2 equiv) [14] .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations